The economic importance of cattle and goats as additional income to farmers - Wiguna, M.A. (1981)
A study of the economic importance of cattle and goats was carried on in upland, rain fed lowland, and irrigate lowland areas. Differences in number of cattle did not influence the percenttage of income from cattle raising. Differences in location influenced income. The percent of farmers' income from cattle was 20.97. 17.21 and 16.03% respective in upland, rain fed and irrigated areas. The shate of goats in the income of farmers indicated that the smaller the number of goats, the higher the percentage contribution to total income. The apparent reason was faster turn-over. The profit from bank loans on the cattle development program (PUTP) was bigger than the profit from leasing systems. The most profitable leasing system for cattle was from the Livestock Service Office (LSD), while for goats was the one from the Social Welfare Office (SWO).